2022
DOI: 10.1149/ma2022-01341386mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Binding Abilities By Incorporating Oxophilic Transition Metals on 3D Nanostructured Ni Arrays for Accelerated Alkaline Hydrogen Evolution Reaction

Abstract: Developing efficient and inexpensive electrocatalysts for the hydrogen evolution reaction (HER) in alkaline water electrolysis plays a key role for renewable hydrogen energy technology. The slow reaction kinetics of HER in alkaline solutions, however, has hampered advances in high-performance hydrogen production. Herein, we investigated the trends in HER activity with respect to the binding energies of Ni-based thin film catalysts by incorporating a series of oxophilic transition metal atoms. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…(e) The increasing oxophilicity may be a reason for the high catalytic activity. For example, Kim et al 70 reported that the incorporation of oxophilic transition metal on threedimensional (3D) nanostructure Ni array accelerates the hydrogen evolution reaction. Jiao and co-workers reported the role of surface oxophilicity in the water splitting catalyzed by copper.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…(e) The increasing oxophilicity may be a reason for the high catalytic activity. For example, Kim et al 70 reported that the incorporation of oxophilic transition metal on threedimensional (3D) nanostructure Ni array accelerates the hydrogen evolution reaction. Jiao and co-workers reported the role of surface oxophilicity in the water splitting catalyzed by copper.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, EIS was also performed to estimate the HER kinetics on the surfaces of the catalysts. 71,72 The lower charge-transfer resistance (R ct ) implies faster electron transfer and the enhanced HER kinetics toward the catalytic reaction. 44,72−74 As shown in the Nyquist plot and equivalent circuit in Figure 3c, the smaller semicircular radius for the Nyquist plot indicates a lower R ct .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…S6 †). 62,63 The small R ct value of the CoCH@Co-MOF-30 demonstrates favorable charge transfer kinetics, therefore implying high HER activity.…”
Section: Resultsmentioning
confidence: 99%